1994
DOI: 10.1021/ma00104a016
|View full text |Cite
|
Sign up to set email alerts
|

One- and Two-Dimensional Nuclear Magnetic Resonance Characterization of Poly(aspartic acid) Prepared by Thermal Polymerization of L-Aspartic Acid

Abstract: It is well-known that thermal treatment of aspartic acid produces poly(anhydr0aspartic acid) (polysuccinimide), which can then be hydrolyzed to sodium polyaspartate. Both polysuccinimide and sodium polyaspartate have been analyzed by a variety of one-and two-dimensional NMR techniques. 'H NMR indicates that sodium polyaspartate invariably contains a 3:l ratio of j3:a linkages, under a variety of synthesis and hydrolysis conditions. NMR and lW3C HMBC data show that the sequencing is random. Residual succinimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 8 publications
8
91
0
7
Order By: Relevance
“…Earlier structural analyses demonstrated that β-Asp units account for 70 % of the total composition of tPAA, indicating that tPAA is composed of a high proportion of β-peptides. The analyses also showed that tPAA contains equivalent moles of D-and L-Asp units, with branching and cross-linking as unnatural structures, in addition to β-Asp units [45][46][47][48][49]. As unnatural structures in polymer materials generally affect the biodegradability of the material, tPAA biodegradability should be carefully considered in its applications.…”
Section: Paamentioning
confidence: 99%
“…Earlier structural analyses demonstrated that β-Asp units account for 70 % of the total composition of tPAA, indicating that tPAA is composed of a high proportion of β-peptides. The analyses also showed that tPAA contains equivalent moles of D-and L-Asp units, with branching and cross-linking as unnatural structures, in addition to β-Asp units [45][46][47][48][49]. As unnatural structures in polymer materials generally affect the biodegradability of the material, tPAA biodegradability should be carefully considered in its applications.…”
Section: Paamentioning
confidence: 99%
“…The reaction yields a melt which is difficult to handle. In NMR and biodegradation studies, these polyaspartates showed less branching and improved biodegradability compared to those prepared without an acid catalyst [31][32][33] (see Chapter 4). In addition, these polyaspartates have a higher molecular mass of approximately 50 000.…”
Section: Solid-phase Thermal Polycondensationmentioning
confidence: 99%
“…In the present study, we reported the acid catalyst polycondensation of aspartic acid with valine product poly-(aspartamide/valine) (PAV) at different molar ratios. Their chemical structures were conformed by 13 C-NMR, DSC, FT-IR, X-ray, and GPC measurements. The effects of light, temperature, humidity, and pH on PHPAV were investigated.…”
Section: Introductionmentioning
confidence: 99%